If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70x + -9y = 0 Solving 70x + -9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9y' to each side of the equation. 70x + -9y + 9y = 0 + 9y Combine like terms: -9y + 9y = 0 70x + 0 = 0 + 9y 70x = 0 + 9y Remove the zero: 70x = 9y Divide each side by '70'. x = 0.1285714286y Simplifying x = 0.1285714286y
| 11-2e=285 | | Y=-2(-3)+7 | | 5x-7x-20=60-8x | | 9xw*4w= | | 7x+6x-42=84-8x | | 126+(x*10)=84+(x*17) | | Y=11/6x-9 | | 7x+6-42=84-8x | | [-4x]x[-8xyz]= | | (3x-9)=73 | | 2+(n*3)=4*n | | (36p^8)^1/2 | | 2/3x=16-4 | | (4x-5)3=38 | | 5x-12x=3x+15+2x | | 3x+15-6x-10=9x-6-3+5 | | 3x+8=-11+2x | | 0=2x^3-6x^2-32x | | 5p-3pq= | | Y=5/4x-13/x | | 16=4+0.363 | | h+3h+4h=200 | | -5=2-5 | | 100x+33y=21 | | z^2-2z+6=2-i | | 3+6n=6 | | 23*23+b*b=26*26 | | y^2=48y | | 5(6d+1)-3d= | | =(x+4)(x+4)(x+4)x | | 4x^3+3x^2-31x+42=0 | | 2a-2+3=5 |